Enhanced photocatalytic activity of gold nanoparticles driven by supramolecular host–guest chemistry. Issue 13 (30th January 2017) - Padilla, Marc; Peccati, Francesca; Bourdelande, José Luis; Solans-Monfort, Xavier; Guirado, Gonzalo; Sodupe, Mariona; Hernando, Jordi
Abstract : Gold nanoparticles coated with cyclodextrins show enhanced plasmon-based photocatalytic activities by promoting catalyst–reactant approximation via supramolecular host–guest complex formation. Abstract : Functionalization of gold nanoparticles with supramolecular hosts allows their plasmon-based photocatalytic activity to be enhanced. This is mainly ascribed to the formation of labile host–guest complexes with the reagent molecules on the metal surface, thus promoting nanoparticle-substrate approximation without interfering with the light-induced catalytic process.